A kind of anti-alkali soft porcelain and preparation method thereof
By using cement-based ceramic waste residue and silicon powder in soft porcelain to form a crosslinked structure, combined with the glass transition temperature characteristics of the emulsion, the problems of alkalinity and laying firmness of soft porcelain are solved, and its strength and flexibility are improved, and the strength and flexibility are improved. The utilization rate of ceramic waste residue.
Patent Information
- Application Number
- CN202411095109.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-12
AI Technical Summary
Existing soft porcelain products are prone to alkaline during use, and have poor lamination firmness and low utilization rate of ceramic waste slag.
Use cement-based ceramic waste residue to replace cement, and combine silicon powder to replace cement-based ceramic waste residue in the surface layer to form a cross-linked structure between the bottom layer and the surface layer, and use the different glass transition temperatures of Emulsion A and Emulsion B to improve strength and flexibility. Add a hooded hydrophobic coating to the surface to prevent calcium hydroxide migration.
It effectively improves the anti-alkali properties and laying firmness of soft porcelain, improves its strength and flexibility, and improves the utilization rate of ceramic waste residue.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of building decoration materials, and in particular to an alkali-resistant soft porcelain and a preparation method thereof. Background Art
[0002] In the field of building decoration materials, traditional tiles have long been dominant due to their hardness, wear resistance and easy cleaning. However, with the continuous advancement of building material technology, the limitations of traditional tiles have gradually emerged, such as their fragility and difficulty in bending during construction.
[0003] In order to solve the above problems, soft porcelain has emerged as a new type of building decoration material. It not only retains the beautiful appearance of traditional ceramic tiles, such as imitation stone and imitation wood grain, but also performs well in flexibility, earthquake resistance and crack resistance, solving the problems of traditional ceramic tiles being fragile and difficult to bend during construction, making it increasingly popular and widely used in scenes such as exterior walls, interior walls and floors.
[0004] At present, soft porcelain products are mainly cement-based soft porcelain. Cement is easy to hydrate to form calcium hydroxide in a humid environment and easily migrate to the surface of the material with water, thereby reacting with carbon dioxide in the air to form white precipitation. That is, cement-based soft porcelain is prone to efflorescence during use.
[0005] In order to solve the efflorescence phenomenon of cement-based soft porcelain, the industry has introduced emulsion-based soft porcelain, that is, a large amount of emulsion is added to the raw materials of soft porcelain instead of cement to avoid the efflorescence phenomenon. However, due to the lack of cement hydration to improve its strength, the structural strength of emulsion-based soft porcelain is poor; and the soft porcelain glue used for paving soft porcelain on the market is mainly suitable for cement-based soft porcelain. The firmness of the emulsion-based soft porcelain after paving with the above-mentioned soft porcelain glue is poor and it is easy to fall off.
[0006] In addition, a large amount of ceramic waste residue is generated during the ceramic production process. The conventional treatment method is generally to pile it up or landfill it, which not only pollutes the environment and causes irreparable damage to the soil, but also causes serious waste of resources.
[0007] In order to overcome the above-mentioned defects, the prior art mainly uses the following technical means to process ceramic waste residue: First, the Chinese invention patent with publication number CN103204663A discloses an artificial stone prepared from solid waste residue, using ceramic waste residue and tile waste to partially or completely replace quartz sand, and obtains an artificial stone with excellent mechanical properties such as fracture modulus, wear resistance, and surface hardness. Second, the Chinese invention patent with publication number CN116462464A discloses a cement-based artificial stone containing artificial stone waste residue and a preparation method thereof, which uses artificial stone waste residue to prepare cement-based artificial stone, improves the early strength and durability of cement-based artificial stone, and effectively alleviates the environmental pressure caused by artificial stone waste residue. In summary, the prior art mainly uses ceramic waste residue to produce artificial stone, and does not involve the use of ceramic waste residue to obtain soft porcelain with anti-eluviation function. Summary of the invention
[0008] The purpose of the present invention is to propose an anti-alkali soft porcelain and a preparation method thereof, to utilize ceramic waste residue in soft porcelain, to improve the strength and flexibility of soft porcelain while effectively improving the alkali efflux phenomenon of soft porcelain and ensuring the firmness of paving, so as to overcome the shortcomings of the prior art.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] An anti-alkali soft porcelain, characterized in that it comprises a bottom layer and a surface layer arranged in sequence from bottom to top; the bottom layer is obtained by solidifying the bottom layer slurry, and the surface layer is obtained by solidifying the surface layer slurry;
[0011] Calculated by weight, the bottom slurry includes the following raw materials: 3-6 parts of cement-based ceramic waste, 30-40 parts of quartz sand, 8-15 parts of quartz powder, 26-40 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 parts of water reducer and 5-8 parts of water;
[0012] Calculated by weight, the surface slurry includes the following raw materials: 30-40 parts of quartz sand, 8-15 parts of quartz powder, 12-20 parts of silicon powder, 15-25 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 part of water reducer and 6-10 parts of water;
[0013] Wherein, the glass transition temperature of the emulsion A is higher than the glass transition temperature of the emulsion B.
[0014] Further, the cement-based ceramic waste residue is artificial stone waste residue, and the chemical composition of the artificial stone waste residue, calculated by mass percentage, includes SiO2 62-70%, Al2O3 5-9%, Fe2O3 1.5-2.5%, CaO 12-18%, MgO 1-1.5%, Na2O 0.2-0.6%, TiO2 0.2-0.3%, K2O 1.2-1.6% and SO3 3.5-4.5%, and the rest is loss on ignition;
[0015] The particle size of the artificial stone waste is less than 3 mm.
[0016] Furthermore, the glass transition temperature of the emulsion A is 20 to 28°C, and the glass transition temperature of the emulsion B is -20 to 10°C.
[0017] Further, the emulsion A includes any one of silicone-acrylic emulsion, pure acrylic emulsion and styrene-acrylic emulsion;
[0018] The emulsion B includes any one of silicone-acrylic emulsion, pure acrylic emulsion and styrene-acrylic emulsion.
[0019] Furthermore, the mesh size of the silicon micropowder is 800 to 2000 mesh;
[0020] The mesh number of the quartz sand is 70-120 meshes, the mesh number of the quartz powder is 200-400 meshes, and the mesh number of the heavy calcium carbonate powder is 200-400 meshes.
[0021] Furthermore, it also includes a finishing layer, which is located on the top of the surface layer, and the finishing layer is obtained by curing the finishing hydrophobic coating;
[0022] Calculated by weight, the top hydrophobic coating includes the following raw materials: 40 to 60 parts of silica sol, 1 to 3 parts of surfactant, 35 to 50 parts of silane coupling agent, 1 to 3 parts of solvent and 0.5 to 2 parts of hydrophobic additive.
[0023] Furthermore, the particle size of the silica sol is 5 to 50 nm.
[0024] Furthermore, the hydrophobic auxiliary agent is a self-crosslinking modified polysiloxane, and the surfactant is a polyethylene glycol type nonionic surfactant.
[0025] Furthermore, the thickness of the bottom layer is 1 to 1.5 mm, the thickness of the surface layer is 1.6 to 2 mm, and the thickness of the overcoat layer is 30 to 90 μm.
[0026] A method for preparing alkali-resistant soft porcelain, used for preparing the above-mentioned alkali-resistant soft porcelain, comprises the following steps:
[0027] S1. According to the formula of the bottom slurry, the water reducing agent and water are mixed in a formula amount to obtain a first mixture; the emulsion A and emulsion B are added to the first mixture and mixed evenly to obtain a first intermediate material; the cement-based ceramic waste residue, quartz sand, quartz powder and heavy calcium carbonate powder are added to the first intermediate material and mixed evenly to obtain a bottom slurry;
[0028] S2. According to the formula of the surface slurry, the water reducing agent and water are mixed in the formula amount to obtain a second mixture; the emulsion A and emulsion B are added to the second mixture and mixed to obtain a second intermediate material; the silicon powder, quartz sand, quartz powder and heavy calcium carbonate powder are added to the second intermediate material and mixed to obtain a surface slurry;
[0029] S3. According to the formula of the overlay hydrophobic coating, the formula amount of silica sol, surfactant, silane coupling agent, solvent and hydrophobic additive are mixed uniformly to obtain an overlay hydrophobic coating;
[0030] S4. Inject the surface layer slurry into the mold, and form a surface layer after curing at 85-110°C for 0.12-0.2h; inject the bottom layer slurry on the surface of the surface layer, and form a bottom layer after curing at 85-110°C for 0.8-0.95h, and obtain a soft porcelain intermediate after demoulding; spray the top hydrophobic coating on the top of the surface layer in the soft porcelain intermediate to form a top layer, and obtain an anti-alkali soft porcelain after curing.
[0031] The technical solution provided by the present invention may include the following beneficial effects:
[0032] 1. Taking advantage of the fact that cement-based ceramic waste residue is used to replace cement in the bottom slurry to reduce the efflorescence phenomenon, combined with the use of silicon powder to replace cement-based ceramic waste residue in the surface slurry, the surface layer obtained by curing the surface slurry has no efflorescence phenomenon, and the surface layer can be used as a blocking layer to cut off the migration of calcium hydroxide, a component that causes efflorescence in the bottom layer. That is, through the mutual cooperation of the bottom layer and the surface layer, it is beneficial to effectively improve the efflorescence phenomenon of soft porcelain and ensure the anti-efflorescence effect of soft porcelain. In addition, because cement-based ceramic waste residue is used in the bottom layer slurry, the bottom layer obtained by curing the bottom layer slurry has a high compatibility with the commonly used adhesive for soft porcelain paving on the market, which is beneficial to improve the firmness of soft porcelain paving.
[0033] 2. In the curing stage of the base slurry of the present technical solution, emulsion A, emulsion B, quartz sand, quartz powder and heavy calcium carbonate powder react to form an organic cross-linked structure, cement-based ceramic waste reacts with quartz sand, quartz powder and heavy calcium carbonate powder to form an inorganic cross-linked structure, and emulsion A, emulsion B, quartz sand, quartz powder, silicon micropowder and heavy calcium carbonate powder in the surface slurry react to form an organic cross-linked structure. The base layer having an organic cross-linked structure and an inorganic cross-linked structure is formed by curing the base layer slurry, and the surface layer slurry is cured to form a surface layer having an organic cross-linked structure. While ensuring the softness of the base layer, the strength of the soft porcelain is improved.
[0034] 3. The technical solution preferably adds emulsion A and emulsion B with different glass transition temperatures to the base slurry and the surface slurry formula, and in the above two formulas, the glass transition temperature of emulsion A is higher than that of emulsion B. The properties of emulsion A to improve strength and emulsion B to improve flexibility are used to ensure the flexibility and strength of the base slurry and the surface slurry, thereby ensuring the flexibility and strength of the soft porcelain. In addition, in order to ensure the flexibility of the soft porcelain, the technical solution specifically makes the addition amount of emulsion B with a low glass transition temperature higher than the addition amount of emulsion A in the base slurry and the surface slurry formula. DETAILED DESCRIPTION
[0035] The technical solution provides an anti-alkali soft porcelain, comprising a bottom layer and a surface layer arranged in sequence from bottom to top; the bottom layer is obtained by solidifying the bottom layer slurry, and the surface layer is obtained by solidifying the surface layer slurry;
[0036] Calculated by weight, the bottom slurry includes the following raw materials: 3-6 parts of cement-based ceramic waste, 30-40 parts of quartz sand, 8-15 parts of quartz powder, 26-40 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 parts of water reducer and 5-8 parts of water;
[0037] Calculated by weight, the surface slurry includes the following raw materials: 30-40 parts of quartz sand, 8-15 parts of quartz powder, 12-20 parts of silicon powder, 15-25 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 part of water reducer and 6-10 parts of water;
[0038] Wherein, the glass transition temperature of the emulsion A is higher than the glass transition temperature of the emulsion B.
[0039] In order to solve the technical problems in the prior art that soft porcelain is prone to alkali efflorescence, has poor paving firmness and has poor utilization rate of ceramic waste, the present technical scheme proposes an alkali-resistant soft porcelain, comprising a base layer and a surface layer arranged in sequence from bottom to top; the base layer is obtained by solidifying a base layer slurry, and the surface layer is obtained by solidifying a surface layer slurry. By optimizing the base layer slurry and the surface layer slurry, while effectively improving the alkali efflorescence phenomenon of the soft porcelain and ensuring the paving firmness, not only the strength and flexibility of the soft porcelain can be improved, but it is also beneficial to improve the utilization rate of ceramic waste.
[0040] First, cement is generally used directly as a cementitious material in the prior art. However, due to the rapid hydration rate of cement, the precipitation rate of the cement hydration product calcium hydroxide is rapid and the precipitation amount is large. It is easy to migrate to the surface of the material along with the water and react with carbon dioxide in the air to form calcium carbonate, thereby causing efflorescence.
[0041] In order to solve the efflorescence phenomenon caused by cement, the present technical solution specifically preferably adds cement-based ceramic waste residue (such as artificial stone waste residue or floor paving stone waste residue, etc.) to the formula. Compared with directly adding cement to the bottom slurry formula, since the cement-based ceramic waste residue is a partially hydrated clinker, the residual cement content inside it is limited. In the subsequent hydration process, the amount of calcium hydroxide released will be greatly reduced, which is conducive to reducing the risk of efflorescence. At the same time, compared with cement, the proportion of cement in cement-based ceramic waste residue is limited, and its hydration reaction rate is relatively slow, which slows down the precipitation rate of calcium hydroxide accordingly, further reducing its accumulation on the surface of soft porcelain, thereby reducing the possibility of efflorescence. In addition, since the cement in the cement-based ceramic waste residue that has not undergone hydration reaction reacts in the aqueous environment of the bottom slurry, it not only generates calcium hydroxide, but also generates calcium silicate gel. The calcium silicate gel is intertwined and entangled with quartz sand, quartz powder, and heavy calcium carbonate powder to form a three-dimensional inorganic cross-linked structure (i.e., microstructure). The slow hydration process allows the hydration product calcium silicate gel more time to diffuse and rearrange inside the bottom layer, which is conducive to forming a denser and more uniform microstructure. It can not only improve the strength and durability of the bottom layer, but also more effectively block the migration of calcium hydroxide and further reduce the occurrence of efflorescence.
[0042] Although the anti-efflorescence performance of soft porcelain can be effectively improved by optimizing the formula of the base slurry, the possibility of efflorescence still exists if the formula of the base slurry is optimized alone, which makes it difficult to meet the actual use requirements. Therefore, the surface slurry is also optimized in this technical solution. Specifically, compared with cement-based ceramic waste, silicon micropowder can not only be used as an aggregate, but also has the advantage of not undergoing hydration reaction to produce efflorescence. Therefore, the surface slurry uses silicon micropowder to replace the cement-based ceramic waste in the base slurry, so that the surface layer obtained by curing the surface slurry has no efflorescence phenomenon, and because the surface layer is located on top of the base layer, it can serve as a blocking layer to cut off the migration of calcium hydroxide, a component in the base layer that causes efflorescence, thereby further reducing the efflorescence phenomenon and ensuring the anti-efflorescence effect of soft porcelain.
[0043] Therefore, the technical solution utilizes the characteristic of using cement-based ceramic waste residue to replace cement in the bottom slurry, thereby reducing the efflorescence phenomenon, and combines the use of silicon micropowder to replace cement-based ceramic waste residue in the surface slurry, so that the surface layer obtained by solidifying the surface slurry has no efflorescence phenomenon, and the surface layer can be used as a blocking layer to cut off the migration of calcium hydroxide, a component that causes efflorescence phenomenon in the bottom layer. That is, through the mutual cooperation between the bottom layer and the surface layer, it is beneficial to effectively improve the efflorescence phenomenon of soft porcelain and ensure the anti-efflorescence effect of soft porcelain. In addition, because cement-based ceramic waste residue is used in the bottom layer slurry, the bottom layer obtained by solidifying the bottom layer slurry has a higher matching degree with the existing adhesive commonly used for soft porcelain paving on the market, which is beneficial to improve the firmness of soft porcelain paving.
[0044] Secondly, the raw materials of the bottom slurry and the surface slurry formula in the technical scheme also include emulsion A, emulsion B, quartz sand, quartz powder and heavy calcium carbonate powder. In the curing stage, the polymers in emulsion A and emulsion B in the bottom slurry and the surface slurry formula maintain a stable dispersion state by electrostatic repulsion and steric hindrance, and the above polymers first gradually approach quartz sand, quartz powder and heavy calcium carbonate powder to form an adsorption layer; afterwards, with the volatilization of water in the bottom slurry and the surface slurry formula in the curing stage, the formed adsorption layer is destroyed, and the above raw materials contact each other to achieve close accumulation; finally, when the curing temperature is higher than the minimum film-forming temperature of emulsion A and emulsion B, the polymers in emulsion A and emulsion B are deformed and aggregated into a film, and at the same time, the molecular chains at the polymer interface diffuse, penetrate and entangle with each other to form a continuous and uniform organic cross-linked structure. That is, during the curing stage, the emulsion A, emulsion B, quartz sand, quartz powder and heavy calcium carbonate powder in the base slurry and the surface slurry formula are agglomerated with each other through physical and chemical reactions to form a continuous and uniform organic cross-linked structure. It should be noted that since the surface slurry formula also includes raw silicon micropowder, the silicon micropowder can also participate in cross-linking curing. Therefore, during the curing stage, the surface slurry actually contains emulsion A, emulsion B, quartz sand, quartz powder, silicon micropowder and heavy calcium carbonate powder, which are agglomerated with each other through physical and chemical reactions to form a continuous and uniform organic cross-linked structure.
[0045] Therefore, in the curing stage of the base slurry of the present technical solution, emulsion A, emulsion B, quartz sand, quartz powder and heavy calcium carbonate powder react to form an organic cross-linked structure, cement-based ceramic waste reacts with quartz sand, quartz powder and heavy calcium carbonate powder to form an inorganic cross-linked structure, and emulsion A, emulsion B, quartz sand, quartz powder, silicon micropowder and heavy calcium carbonate powder in the surface layer slurry react to form an organic cross-linked structure. The base layer having an organic cross-linked structure and an inorganic cross-linked structure is formed by curing the base layer slurry, and the surface layer slurry is cured to form a surface layer having an organic cross-linked structure. While ensuring the softness of the base layer, the strength of the soft porcelain is improved.
[0046] Furthermore, the polymer hardness and toughness formed by emulsions with different glass transition temperatures are different, and the higher the glass transition temperature of the emulsion, the higher the rigidity of the polymer chain formed after solidification, which is more conducive to improving the strength of the slurry formula; the lower the glass transition temperature of the emulsion, the higher the flexibility of the polymer chain formed after solidification, which is more conducive to improving the flexibility of the slurry formula. Therefore, the technical solution preferably adds emulsions A and B with different glass transition temperatures to the bottom slurry and surface slurry formulas, and in the above two formulas, the glass transition temperature of emulsion A is higher than that of emulsion B. The properties of emulsion A to improve strength and emulsion B to improve flexibility are used to ensure the flexibility and strength of the bottom slurry and surface slurry, thereby ensuring the flexibility and strength of soft porcelain. In addition, in order to ensure the flexibility of soft porcelain, the technical solution specifically makes the addition amount of emulsion B with a low glass transition temperature higher than the addition amount of emulsion A in the bottom slurry and surface slurry formulas.
[0047] Furthermore, in addition to participating in the reaction to generate a cross-linked structure, the quartz sand, quartz powder and heavy calcium carbonate powder in the bottom slurry and the surface slurry of the technical solution, as a coarse aggregate and as a fine aggregate, cooperate with each other to form the skeleton of the bottom and surface layers, providing the function of supporting soft porcelain; the high filling property of heavy calcium carbonate powder is conducive to its support of the bottom and surface layers, improving the hardness and dimensional stability of soft porcelain, and at the same time, heavy calcium carbonate powder can improve the fluidity and plasticity of the bottom slurry and the surface slurry, making it easier for soft porcelain to be molded into various shapes during processing, which is conducive to improving the processing efficiency of soft porcelain and reducing the processing difficulty. In addition, the surface slurry formula also includes silicon micropowder, which, in addition to realizing its role as an aggregate, is also conducive to dispersing other raw materials in the surface slurry, avoiding the agglomeration and precipitation of other raw materials, and causing the performance of the surface slurry to decrease. At the same time, silicon micropowder can also be used as a filler to fill the micropores in the surface layer, thereby significantly improving the density of soft porcelain and then improving its strength.
[0048] Finally, calculated by weight, the base slurry includes the following raw materials: 3-6 parts of cement-based ceramic waste, 30-40 parts of quartz sand, 8-15 parts of quartz powder, 26-40 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 parts of water reducer and 5-8 parts of water; calculated by weight, the surface layer slurry includes the following raw materials: 30-40 parts of quartz sand, 8-15 parts of quartz powder, 12-20 parts of silicon powder, 15-25 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 parts of water reducer and 6-10 parts of water. Although cement-based ceramic waste is partially hydrated clinker with limited residual cement content, if the amount of cement-based ceramic waste added is too large, the amount of cement in the base slurry will still be relatively large, and the efflorescence phenomenon cannot be effectively reduced. Since the base layer obtained by solidifying the base slurry is in direct contact with the adhesive for soft porcelain paving, if the amount of cement-based ceramic waste added is too small, it will affect the firmness of the soft porcelain paving, and will also lead to limited cement hydration effect of the base slurry, thereby affecting the strength of the soft porcelain.
[0049] Furthermore, since the silicon powder in the surface layer slurry can also play a filling role, the amount of heavy calcium carbonate powder added in the surface layer slurry is lower than that in the bottom layer slurry, which is beneficial to ensure the performance of soft porcelain at a lower cost.
[0050] In addition, the technical scheme limits the addition amount of each component of the base slurry and the surface layer slurry. On the one hand, it is beneficial to adjust the fluidity of the base slurry and the surface layer slurry, facilitate production and processing, and improve production efficiency; on the other hand, it is also beneficial to form a dense chamber accumulation of the remaining raw materials after the base slurry and the surface layer slurry are solidified, thereby ensuring the performance of the soft porcelain.
[0051] Therefore, in the technical scheme, cement-based ceramic waste residue is used instead of cement by coordinating the cement-based ceramic waste residue, quartz sand, quartz powder, heavy calcium carbonate powder, emulsion A, emulsion B, water reducer and water in the base slurry, and the quartz sand, quartz powder, silicon micropowder, heavy calcium carbonate powder, emulsion A, emulsion B, water reducer and water in the surface slurry, and the addition amount of each raw material in the base slurry and the surface slurry is limited, which not only turns waste into treasure and makes full use of the cement-based ceramic waste residue, but also makes the base layer having an organic cross-linked structure and an inorganic cross-linked structure obtained after the base slurry is solidified, and makes the surface layer having an organic cross-linked structure formed after the surface slurry is solidified. On the premise of effectively improving the alkali efflux phenomenon of soft porcelain and the firmness of paving, it can not only improve the strength and flexibility of soft porcelain, but also help to improve the utilization rate of ceramic waste residue.
[0052] Furthermore, in the technical scheme, the base slurry and the surface layer slurry formulas both contain raw materials such as quartz sand, quartz powder, heavy calcium carbonate powder, emulsion A, emulsion B, water reducer and water, making the formula systems of the base slurry and the surface layer slurry relatively close, which is beneficial to ensure the bonding strength between the base layer obtained by curing the base slurry and the surface layer obtained by curing the surface layer slurry, and avoid affecting the performance of soft porcelain due to poor bonding strength.
[0053] Preferably, both the bottom slurry and the surface slurry further include a defoaming agent;
[0054] Calculated by weight, the bottom slurry includes the following raw materials: 3-6 parts of cement-based ceramic waste, 30-40 parts of quartz sand, 8-15 parts of quartz powder, 26-40 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 parts of water reducer, 5-8 parts of water and 0.05-0.2 parts of defoamer;
[0055] Calculated by mass, the surface layer slurry includes the following raw materials: 30-40 parts of quartz sand, 8-15 parts of quartz powder, 12-20 parts of silicon micropowder, 15-25 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 part of water reducer, 6-10 parts of water and 0.05-0.2 part of defoaming agent.
[0056] In a preferred embodiment of the present technical solution, defoaming agents are added to both the bottom slurry and the surface slurry to eliminate bubbles in the bottom slurry and the surface slurry, thereby increasing the density of the soft porcelain product and ensuring its appearance.
[0057] Preferably, the defoamer is NXZ defoamer.
[0058] In a preferred embodiment of the present technical solution, the defoamer is NXZ defoamer (i.e., mineral oil hydrophobic gas phase silica and metal soap defoamer). NXZ defoamer not only has excellent defoaming and foam suppression effects, but also has good compatibility with the slurry system of the present technical solution, ensuring the performance of the bottom slurry and the surface slurry.
[0059] Preferably, the water reducing agents in the base slurry and the surface slurry are both polycarboxylic acid water reducing agents.
[0060] In a preferred embodiment of the present technical solution, both the bottom slurry and the surface slurry contain polycarboxylic acid water reducer, which can reduce water consumption on the one hand, and help improve the strength and flexibility of soft porcelain on the other hand, ensuring product performance.
[0061] It is further explained that the cement-based ceramic waste residue is artificial stone waste residue, and the chemical composition of the artificial stone waste residue, calculated by mass percentage, includes SiO2 62-70%, Al2O3 5-9%, Fe2O3 1.5-2.5%, CaO 12-18%, MgO 1-1.5%, Na2O 0.2-0.6%, TiO2 0.2-0.3%, K2O 1.2-1.6% and SO3 3.5-4.5%, and the rest is loss on ignition;
[0062] The particle size of the artificial stone waste is less than 3 mm.
[0063] Calculated by mass percentage, the chemical composition of the commonly used cement includes CaO 64-67%, SiO2 20-23%, Al2O3 4-8% and Fe2O3 3-6%, and the rest is the loss on ignition. Therefore, in a preferred embodiment of the present technical solution, the artificial stone waste slag with the preferred chemical composition including SiO2 62-70%, Al2O3 5-9%, Fe2O3 1.5-2.5%, CaO 12-18%, MgO 1-1.5%, Na2O 0.2-0.6%, TiO2 0.2-0.3%, K2O 1.2-1.6% and SO3 3.5-4.5% is used as the cement-based ceramic waste slag of the present technical solution. Compared with the commonly used cement, the CaO content is greatly reduced, so as to greatly improve the efflorescence phenomenon under the premise of ensuring the soft porcelain performance.
[0064] Furthermore, the particle size of the artificial stone waste is less than 3 mm, which is beneficial to improving its utilization rate on the one hand, and on the other hand, is beneficial to fully utilizing the cement remaining in the artificial stone waste to ensure the strength of the product.
[0065] It is further described that the glass transition temperature of the emulsion A is 20 to 28°C, and the glass transition temperature of the emulsion B is -20 to 10°C.
[0066] This technical solution optimizes the glass transition temperature of emulsion A and emulsion B, and the glass transition temperature of emulsion A and emulsion B is quite different, which is beneficial to ensure the curing and cross-linking effect of emulsion A and emulsion B, and improves the strength of soft porcelain, and is also beneficial to improve the flexibility of soft porcelain.
[0067] It is further described that the emulsion A includes any one of silicone acrylic emulsion, pure acrylic emulsion and styrene acrylic emulsion;
[0068] The emulsion B includes any one of silicone-acrylic emulsion, pure acrylic emulsion and styrene-acrylic emulsion.
[0069] Silicone-acrylic emulsion has good aging resistance, good flexibility and strength; pure acrylic emulsion has good weather resistance, aging resistance and color and gloss retention; styrene-acrylic emulsion is a milky white liquid with good adhesion and good water resistance, oil resistance, heat resistance and aging resistance. Therefore, in a preferred embodiment of the present technical solution, emulsion A includes any one of silicone-acrylic emulsion, pure acrylic emulsion and styrene-acrylic emulsion, and emulsion B includes any one of silicone-acrylic emulsion, pure acrylic emulsion and styrene-acrylic emulsion to ensure the performance of soft porcelain.
[0070] Preferably, emulsion A is a silicone-acrylic emulsion; and emulsion B is a silicone-acrylic emulsion.
[0071] It is further described that the mesh size of the silicon micropowder is 800 to 2000 mesh;
[0072] The mesh number of the quartz sand is 70-120 meshes, the mesh number of the quartz powder is 200-400 meshes, and the mesh number of the heavy calcium carbonate powder is 200-400 meshes.
[0073] In a preferred embodiment of the present technical solution, optimizing the mesh size of the silicon micropowder is helpful to ensure that its performance is optimal, thereby ensuring the performance of the surface layer slurry.
[0074] Furthermore, by limiting the mesh size of quartz sand, quartz powder and heavy calcium carbonate powder, it is beneficial to increase the packing density of the remaining raw materials after the base layer slurry and the surface layer slurry are solidified, so that both the base layer and the surface layer form a dense and stable structure, thereby improving its strength while ensuring the flexibility of the soft porcelain.
[0075] Further, it further comprises a finishing layer, the finishing layer is located on the top of the surface layer, and the finishing layer is obtained by curing the finishing hydrophobic coating;
[0076] Calculated by weight, the top hydrophobic coating includes the following raw materials: 40 to 60 parts of silica sol, 1 to 3 parts of surfactant, 35 to 50 parts of silane coupling agent, 1 to 3 parts of solvent and 0.5 to 2 parts of hydrophobic additive.
[0077] In a preferred embodiment of the present technical solution, a covering layer is provided, and the surface layer and the covering layer cooperate with each other to form a second blocking layer that cuts off the migration of calcium hydroxide, a component that causes efflorescence in the bottom layer, thereby further reducing the efflorescence phenomenon and helping to improve the anti-efflorescence effect of soft porcelain.
[0078] Specifically, the raw materials of the hydrophobic coating for the topcoat include silica sol, surfactant, silane coupling agent, solvent and hydrophobic additive. Among them, the charge on the surface of silica sol attracts the polar groups in the silane coupling agent, and the silane coupling agent contains silicon oxygen bonds, which is conducive to the interaction between silica sol and the silane coupling agent through electrostatic adsorption and chemical bonding to form a uniform and dense film layer; in addition, the high specific surface area and porous characteristics of silica sol provide good attachment points and skeleton support for the silane coupling agent, and the molecular chains of the silane coupling agent are intertwined and entangled on the skeleton of the inorganic silica sol, so that the two form a three-dimensional network structure. That is, the silica sol and the silane coupling agent react with each other to make the topcoat a film layer with a three-dimensional network structure containing silicon oxygen bonds, so that the topcoat not only has a high bonding strength with the surface layer, but also has good hydrophobicity on the premise of improving the strength of the soft porcelain. The hydrophobicity of the covering layer effectively prevents the flow of water, avoids the migration of calcium hydroxide to the surface of the soft porcelain with the water, and then blocks the migration path of calcium hydroxide, which is beneficial to reduce the occurrence of efflorescence. At the same time, the hydrophobicity of the covering layer also reduces the contact opportunity between external moisture and cement-based ceramic waste in the underlying layer, reduces the risk of calcium hydroxide generation in the soft porcelain during use, and further reduces the risk of efflorescence of the soft porcelain.
[0079] Further, the raw materials of the top hydrophobic coating also include surfactants, solvents and hydrophobic additives. Silica sol is a water-soluble raw material, while silane coupling agents and hydrophobic additives are oil-soluble raw materials. The mutual solubility of oil-soluble raw materials and water-soluble raw materials is poor. The surfactant is conducive to the dispersion stability of silica sol, silane coupling agent and hydrophobic additive in the solvent, and promotes the mutual dissolution of silica sol and silane coupling agent, and then a cross-linking reaction occurs to ensure the performance of the mask layer. At the same time, the surfactant is also conducive to the top layer obtained after the top hydrophobic coating is cured to have more excellent hydrophobicity due to its lower surface energy. The hydrophobic additive also has a lower surface energy, which can reduce the surface tension of the top layer obtained after the top hydrophobic coating is cured, so that the top layer has a stronger hydrophobic property.
[0080] Therefore, the topcoat hydrophobic coating in the present technical scheme cooperates with each other through silica sol, surfactant, silane coupling agent, solvent and hydrophobic additive, and limits the addition amount of each raw material, which is beneficial to ensure that the topcoat obtained after the topcoat hydrophobic coating is cured not only has a high bonding strength with the surface layer, but also has good hydrophobicity while improving the strength of the soft porcelain, which is beneficial to reduce the occurrence of alkali efflux.
[0081] Preferably, the silane coupling agent is any one of methyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane; and the solvent is any one of water, formic acid, acetic acid, tert-butanol, n-butanol and n-propanol.
[0082] It is further explained that the particle size of the silica sol is 5 to 50 nm.
[0083] Since the silica sol with a particle size of 5 to 50 nm has a large specific surface area and a very strong adsorption capacity, it is conducive to reacting with the silane coupling agent to form a three-dimensional network structure containing silicon-oxygen bonds. Therefore, the technical solution limits the particle size of the silica sol to 5 to 50 nm to ensure the performance of the overcoat layer.
[0084] It is further described that the hydrophobic auxiliary agent is a self-crosslinking modified polysiloxane, and the surfactant is a polyethylene glycol type nonionic surfactant.
[0085] Since the self-crosslinking modified polysiloxane can not only reduce the surface tension of the topcoat obtained after the topcoat hydrophobic coating is cured, but also form a three-dimensional network structure with silica sol and silane coupling agent, thereby further enhancing the relevant properties of the topcoat. Therefore, in a preferred embodiment of the present technical solution, the hydrophobic auxiliary agent is limited to a self-crosslinking modified polysiloxane, which is conducive to improving the relevant properties of soft porcelain.
[0086] Polyethylene glycol nonionic surfactants are highly stable and are a type of nonionic surfactant formed by connecting polyethylene glycol (PEG) or its derivatives as hydrophilic groups with various hydrophobic groups through chemical bonds. They play the role of water-oil transfer and connection, which is beneficial to improving the dispersion stability of water-soluble raw materials (silica sol) and oil-soluble raw materials (silane coupling agent and hydrophobic auxiliary agent) in the top hydrophobic coating in the solvent. Therefore, the technical solution preferably adds polyethylene glycol nonionic surfactants as surfactants to ensure the performance of the top hydrophobic coating.
[0087] Preferably, the self-crosslinking modified polysiloxane is γ-methacryloxypropyltrimethoxysilane.
[0088] It is further described that the thickness of the bottom layer is 1 to 1.5 mm, the thickness of the surface layer is 1.6 to 2 mm, and the thickness of the overcoat layer is 30 to 90 μm.
[0089] In a preferred embodiment of the present technical solution, by limiting the thickness of the surface layer to be greater than that of the bottom layer, the amount of calcium hydroxide generated in the bottom layer is reduced, and the surface layer has a stronger ability to block the migration of calcium hydroxide, a component that causes efflorescence, which is beneficial to improving the anti-efflorescence performance of the soft porcelain. In addition, if the thickness of the overcoat layer is too thick, the bonding strength between it and the surface layer will decrease. Therefore, in a preferred embodiment of the present technical solution, the thickness of the surface layer is thicker than that of the bottom layer, and the thickness of the bottom layer, the surface layer and the overcoat layer are limited to ensure that the thickness of the soft porcelain is moderate, which, on the one hand, reduces its production cost and transportation cost; on the other hand, it is beneficial to ensure that the soft porcelain is easy to lay and its paving firmness is ensured under the premise of ensuring the performance of the soft porcelain.
[0090] A method for preparing alkali-resistant soft porcelain, used for preparing the above-mentioned alkali-resistant soft porcelain, comprises the following steps:
[0091] S1. According to the formula of the bottom slurry, the water reducing agent and water are mixed in a formula amount to obtain a first mixture; the emulsion A and emulsion B are added to the first mixture and mixed evenly to obtain a first intermediate material; the cement-based ceramic waste residue, quartz sand, quartz powder and heavy calcium carbonate powder are added to the first intermediate material and mixed evenly to obtain a bottom slurry;
[0092] S2. According to the formula of the surface slurry, the water reducing agent and water are mixed in the formula amount to obtain a second mixture; the emulsion A and emulsion B are added to the second mixture and mixed to obtain a second intermediate material; the silicon powder, quartz sand, quartz powder and heavy calcium carbonate powder are added to the second intermediate material and mixed to obtain a surface slurry;
[0093] S3. According to the formula of the overlay hydrophobic coating, the formula amount of silica sol, surfactant, silane coupling agent, solvent and hydrophobic additive are mixed uniformly to obtain an overlay hydrophobic coating;
[0094] S4. Inject the surface layer slurry into the mold, and form a surface layer after curing at 85-110°C for 0.12-0.2h; inject the bottom layer slurry on the surface of the surface layer, and form a bottom layer after curing at 85-110°C for 0.8-0.95h, and obtain a soft porcelain intermediate after demoulding; spray the top hydrophobic coating on the top of the surface layer in the soft porcelain intermediate to form a top layer, and obtain an anti-alkali soft porcelain after curing.
[0095] The technical solution also proposes a method for preparing alkali-resistant soft porcelain, which has simple steps and strong operability, and is conducive to ensuring the relevant properties of the soft porcelain during the preparation process.
[0096] Specifically, in the technical solution, by optimizing the curing temperature and curing time of the base slurry and the surface slurry, it is beneficial to ensure that the two are completely cured, thereby ensuring the performance of the product. Specifically, in order to make the surface layer reach a state of being dry but not completely cured, and to ensure the bonding strength between the base layer and the surface layer, after the surface layer slurry is injected into the mold, it needs to be cured at 85 to 110°C for 0.12 to 0.2h. In addition, in order to ensure the performance of the soft porcelain, after the base layer slurry is injected into the surface of the surface layer, it needs to be cured at 85 to 110°C for 0.8 to 0.95h, that is, the curing time after injecting the base layer slurry is longer than the time for injecting the surface layer slurry, which is beneficial to completely cure the base layer and the surface layer, and avoid incomplete curing that affects the performance of the soft porcelain.
[0097] It should be further explained that, since the glass fiber mesh is woven from glass fiber yarns, it has higher strength. When the glass fiber mesh is applied to the soft porcelain structure, it can significantly improve the overall strength of the soft porcelain, so that the soft porcelain material can withstand greater pressure and impact force, and reduce the risk of cracking and deformation. At the same time, the glass fiber mesh has excellent flexibility and plasticity, and can adapt to various complex building surfaces to form a smooth and seamless decorative effect, ensuring its decorativeness. Therefore, the preparation step of the bottom layer in step S4 of the present technical solution can also be: injecting the bottom layer slurry on the surface of the surface layer, and paving the glass fiber mesh, and curing it at 85-110°C for 0.8-0.95h to form the bottom layer. By adding the glass fiber mesh, it is beneficial to improve the flexibility and strength of the soft porcelain.
[0098] Preferably, the curing method of the top hydrophobic coating is any one of curing at room temperature for 6 to 7 hours and curing at 60 to 70° C. for 0.8 to 1.2 hours, so that the curing method of the top hydrophobic coating is flexible and can be selected according to actual needs, thereby improving production flexibility.
[0099] Preferably, in step S4, the inner wall of the mold is provided with a finishing texture.
[0100] In a preferred embodiment of the present technical solution, by limiting the inner wall of the mold to be provided with a finishing texture, a certain texture effect can be produced on the surface of the soft porcelain, thereby improving the appearance texture of the soft porcelain and increasing the added value of the product.
[0101] Performance Test:
[0102] Flexibility: Refer to the standard "JC / T 2219-2014 Modified Inorganic Powder Composite Building Facing Sheet" to observe whether there are cracks or fractures at the bending part of the specimen surface.
[0103] Tensile strength: stick the soft porcelain and the cured specimen together with a high-strength adhesive, cut the soft porcelain along the fixture to the base layer so that the test area is (40×40) mm, install the specimen with the tensile fixture on the testing machine, keep the center line of the specimen surface in the vertical direction and the center of the testing machine fixture in line, stretch at a speed of (5±1) mm / min until the soft porcelain is destroyed, record the maximum tensile force when the soft porcelain is destroyed, and calculate the tensile strength of the soft porcelain according to σ=F / (a×b).
[0104] Anti-efflorescence: Prepare samples with reference to the standard "JG / T 210-2007 Primer for Interior and Exterior Walls of Buildings". Brush the surface of the sample with iron blue color developing solution (prepared with polyvinyl alcohol 1788 and LA09-03 iron blue pigment in a mass ratio of 4:1), and then soak it in water. Observe and record the percentage of surface discoloration area of the sample after 30 days, 60 days and 100 days. If the percentage of surface discoloration area of the sample at the three times is ≤10%, the anti-efflorescence performance is qualified.
[0105] Laying firmness: After laying the soft porcelain with Dongpeng G100 tile adhesive produced by Guangdong Dongpeng Home Furnishing Co., Ltd., the five-point knocking test method is adopted, that is, knocking on the four corners and the center of the tile respectively, and judging whether there are hollows by the changes in sound. If there are no hollows, the laying firmness is qualified.
[0106] Example 1
[0107] A method for preparing alkali-resistant soft porcelain comprises the following steps:
[0108] S1. According to the formula of the bottom slurry, 0.5 parts of polycarboxylic acid water reducer and 8 parts of water are mixed evenly to obtain a first mixture; 3 parts of silicone acrylic emulsion with a glass transition temperature of 20 to 28°C and 6 parts of silicone acrylic emulsion with a glass transition temperature of -20 to 10°C are added to the first mixture and mixed evenly to obtain a first intermediate material; 4 parts of artificial stone waste with a particle size of 2.5 mm, 35 parts of quartz sand with a mesh of 100 mesh, 10 parts of quartz powder with a mesh of 300 mesh and 35 parts of heavy calcium carbonate powder with a mesh of 250 mesh are added to the first intermediate material and mixed evenly to obtain a bottom slurry; wherein, calculated by mass percentage, the chemical composition of the artificial stone waste includes SiO2 68.12%, Al2O3 6.32%, Fe2O3 1.87%, CaO 15.32%, MgO 1.36%, Na2O 0.37%, TiO2 0.21%, K2O 1.56% and SO3 3.89%, the rest is loss on ignition;
[0109] S2. According to the formula of the surface slurry, 0.5 parts of polycarboxylate water reducer and 10 parts of water are mixed evenly to obtain a second mixture; 3 parts of silicone acrylic emulsion with a glass transition temperature of 20 to 28°C and 6 parts of silicone acrylic emulsion with a glass transition temperature of -20 to 10°C are added to the second mixture and mixed evenly to obtain a second intermediate material; 20 parts of 1000 mesh silica powder, 35 parts of 100 mesh quartz sand, 10 parts of 300 mesh quartz powder and 15 parts of 250 mesh heavy calcium carbonate powder are added to the second intermediate material and mixed evenly to obtain a surface slurry;
[0110] S3. According to the formula of the overcoat hydrophobic coating, 50 parts of silica sol having a particle size of 25 nm, 2 parts of polyethylene glycol-type nonionic surfactant, 40 parts of methyltriethoxysilane, 2 parts of acetic acid and 1 part of γ-methacryloxypropyltrimethoxysilane were mixed to obtain an overcoat hydrophobic coating;
[0111] S4. The surface layer slurry is injected into the mold, and after curing at 100°C for 0.2h, a surface layer with a thickness of 2mm is formed; the bottom layer slurry is injected on the surface of the surface layer, and after curing at 100°C for 0.8h, a bottom layer with a thickness of 1.5mm is formed, and a soft porcelain intermediate is obtained after demolding; a topcoat hydrophobic coating is sprayed on the top of the surface layer in the soft porcelain intermediate to form a topcoat with a thickness of 70μm, and after curing at room temperature for 6-7h, an alkali-resistant soft porcelain is obtained.
[0112] Example 2
[0113] A method for preparing alkali-resistant soft porcelain comprises the following steps:
[0114] S1. According to the formula of the bottom slurry, 1 part of polycarboxylic acid water reducer and 6 parts of water are mixed evenly to obtain a first mixture; 4 parts of pure acrylic emulsion with a glass transition temperature of 20-28°C and 8 parts of pure acrylic emulsion with a glass transition temperature of -20-10°C are added to the first mixture and mixed evenly to obtain a first intermediate material; 6 parts of artificial stone waste with a particle size of 2.8 mm, 30 parts of quartz sand with a mesh of 80 mesh, 15 parts of quartz powder with a mesh of 200 mesh and 31.5 parts of heavy calcium carbonate powder with a mesh of 400 mesh are added to the first intermediate material and mixed evenly to obtain a bottom slurry; wherein, calculated by mass percentage, the chemical composition of the artificial stone waste includes SiO2 68.12 parts, Al2O3 6.32%, Fe2O3 1.87%, CaO 15.32%, MgO 1.36%, Na2O 0.37%, TiO2 0.21%, K2O 1.56% and SO33.89%, the rest is loss on ignition;
[0115] S2. According to the formula of the surface slurry, 1 part of polycarboxylate water reducer and 8 parts of water are mixed evenly to obtain a second mixture; 4 parts of pure acrylic emulsion with a glass transition temperature of 20 to 28°C and 8 parts of pure acrylic emulsion with a glass transition temperature of -20 to 10°C are added to the second mixture and mixed evenly to obtain a second intermediate material; 12 parts of silica powder with a mesh number of 800 to 2000 mesh, 30 parts of quartz sand with a mesh number of 80 mesh, 15 parts of quartz powder with a mesh number of 200 mesh and 20 parts of heavy calcium carbonate powder with a mesh number of 400 mesh are added to the second intermediate material and mixed evenly to obtain a surface slurry;
[0116] S3. According to the formula of the overcoat hydrophobic coating, 45 parts of silica sol having a particle size of 45 nm, 1 part of polyethylene glycol-type nonionic surfactant, 45 parts of γ-aminopropyl triethoxysilane, 3 parts of tert-butyl alcohol and 2 parts of γ-methacryloxypropyl trimethoxysilane were mixed to obtain an overcoat hydrophobic coating;
[0117] S4. The surface layer slurry is injected into the mold, and after curing at 90°C for 0.2h, a surface layer with a thickness of 1.6mm is formed; the bottom layer slurry is injected on the surface of the surface layer, and after curing at 110°C for 0.8h, a bottom layer with a thickness of 1.4mm is formed, and a soft porcelain intermediate is obtained after demolding; a topcoat hydrophobic coating is sprayed on the top of the surface layer in the soft porcelain intermediate to form a topcoat with a thickness of 60μm, and after curing at 60-70°C for 0.8-1.2h, an anti-alkali soft porcelain is obtained.
[0118] Example 3
[0119] A method for preparing alkali-resistant soft porcelain comprises the following steps:
[0120] S1. According to the formula of the bottom slurry, 0.5 parts of polycarboxylic acid water reducer and 5 parts of water are mixed evenly to obtain a first mixture; 2 parts of styrene-acrylic emulsion with a glass transition temperature of 20-28°C and 5 parts of styrene-acrylic emulsion with a glass transition temperature of -20-10°C are added to the first mixture and mixed evenly to obtain a first intermediate material; 3 parts of artificial stone waste with a particle size of 2.6 mm, 40 parts of quartz sand with a mesh of 120 mesh, 8 parts of quartz powder with a mesh of 380 mesh and 38 parts of heavy calcium carbonate powder with a mesh of 350 mesh are added to the first intermediate material and mixed evenly to obtain a bottom slurry; wherein, calculated by mass percentage, the chemical composition of the artificial stone waste includes SiO2 68.12%, Al2O3 6.32%, Fe2O3 1.87%, CaO 15.32%, MgO 1.36%, Na2O 0.37%, TiO20.21%, K2O1.56% and SO3 3.89%, the rest is loss on ignition;
[0121] S2. According to the formula of the surface slurry, 0.5 parts of polycarboxylate water reducer and 6 parts of water are mixed evenly to obtain a second mixture; 2 parts of styrene-acrylic emulsion with a glass transition temperature of 20 to 28°C and 5 parts of styrene-acrylic emulsion with a glass transition temperature of -20 to 10°C are added to the second mixture and mixed evenly to obtain a second intermediate material; 17 parts of silica powder with a mesh number of 800 to 2000 mesh, 40 parts of quartz sand with a mesh number of 120 mesh, 8 parts of quartz powder with a mesh number of 380 mesh and 20 parts of heavy calcium carbonate powder with a mesh number of 350 mesh are added to the second intermediate material and mixed evenly to obtain a surface slurry;
[0122] S3. According to the formula of the overlay hydrophobic coating, 58 parts of silica sol having a particle size of 15 nm, 3 parts of polyethylene glycol-type nonionic surfactant, 35 parts of γ-glycidyloxypropyl trimethoxysilane, 3 parts of n-butanol and 0.5 parts of γ-methacryloxypropyl trimethoxysilane were mixed to obtain an overlay hydrophobic coating;
[0123] S4. The surface layer slurry is injected into the mold, and after curing at 105°C for 0.16h, a surface layer with a thickness of 1.6mm is formed; the bottom layer slurry is injected on the surface of the surface layer, and after curing at 110°C for 0.9h, a bottom layer with a thickness of 1.3mm is formed, and a soft porcelain intermediate is obtained after demolding; a topcoat hydrophobic coating is sprayed on the top of the surface layer in the soft porcelain intermediate to form a topcoat with a thickness of 45μm, and after curing at room temperature for 6-7h, an alkali-resistant soft porcelain is obtained.
[0124] Comparative group
[0125] Comparative Example 1
[0126] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that no surface layer is provided in Comparative Example 1.
[0127] Comparative Example 2
[0128] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that no bottom layer is provided in Comparative Example 2.
[0129] Comparative Example 3
[0130] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 1, except that cement-based ceramic waste residue is not added to the bottom slurry formula in Comparative Example 3.
[0131] Comparative Example 4
[0132] The preparation method and raw materials of Comparative Example 4 are the same as those of Example 1, except that cement is used instead of cement-based ceramic waste in the base slurry formula of Comparative Example 4, that is, in Comparative Example 4, the base slurry includes the following raw materials: 4 parts of cement, 35 parts of quartz sand with a mesh size of 100 mesh, 10 parts of quartz powder with a mesh size of 300 mesh, 35 parts of heavy calcium carbonate powder with a mesh size of 250 mesh, 3 parts of silicone-acrylic emulsion with a glass transition temperature of 20 to 28°C, 6 parts of silicone-acrylic emulsion with a glass transition temperature of -20 to 10°C, 0.5 parts of polycarboxylic acid water reducer and 8 parts of water.
[0133] The soft porcelain was prepared by the preparation methods in the above embodiment and comparative example respectively, and the obtained soft porcelain was tested for flexibility, tensile strength, laying firmness and anti-alkali performance. The results are shown in Table 1 below.
[0134] Table 1 Test results of relevant properties of soft porcelain
[0135]
[0136] From the performance test results in Table 1, it can be seen that the soft porcelain prepared by the preparation method of the anti-alkali soft porcelain in the technical scheme has a tensile strength of >8.5MPa, no cracks on the surface, and qualified anti-alkali performance. The strength and flexibility are improved while effectively improving the soft porcelain alkali efflux phenomenon and paving firmness.
[0137] Since no surface layer is provided in Comparative Example 1, the anti-efflorescence performance, strength and flexibility of the soft porcelain are all reduced.
[0138] In Comparative Example 2, since no bottom layer is provided, the strength, flexibility and paving firmness of the soft porcelain are all reduced.
[0139] In Comparative Example 3, since no cement-based ceramic waste residue was added to the bottom slurry, the bottom layer obtained by curing the bottom slurry had poor matching with the existing soft porcelain glue for soft porcelain paving, and the paving firmness was poor. In addition, since no cement-based ceramic waste residue was added to the bottom slurry, it was unable to realize the cement hydration reaction to form an inorganic cross-linked structure, resulting in a decrease in the strength of the soft porcelain.
[0140] In Comparative Example 4, cement is used to replace cement-based ceramic waste residue in the bottom slurry formula, resulting in serious cement hydration phenomenon and poor anti-efflorescence performance. In addition, using cement to replace cement-based ceramic waste residue is conducive to increasing the strength of the bottom layer and weakening its flexibility, resulting in increased strength of soft porcelain and reduced flexibility.
[0141] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. An anti-alkali soft porcelain, characterized in that: It comprises a bottom layer and a surface layer arranged in sequence from bottom to top; the bottom layer is obtained by solidifying the bottom layer slurry, and the surface layer is obtained by solidifying the surface layer slurry; Calculated by weight, the bottom slurry includes the following raw materials: 3-6 parts of cement-based ceramic waste, 30-40 parts of quartz sand, 8-15 parts of quartz powder, 26-40 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 parts of water reducer and 5-8 parts of water; Calculated by weight, the surface slurry includes the following raw materials: 30-40 parts of quartz sand, 8-15 parts of quartz powder, 12-20 parts of silicon powder, 15-25 parts of heavy calcium carbonate powder, 2-4 parts of emulsion A, 5-8 parts of emulsion B, 0.2-1 part of water reducer and 6-10 parts of water; Wherein, the glass transition temperature of the emulsion A is 20 to 28°C, and the glass transition temperature of the emulsion B is -20 to 10°C; The cement-based ceramic waste slag is artificial stone waste slag, and calculated by mass percentage, the chemical composition of the artificial stone waste slag includes SiO2 62-70%, Al2O3 5-9%, Fe2O3 1.5-2.5%, CaO 12-18%, MgO 1-1.5%, Na2O 0.2-0.6%, TiO2 0.2-0.3%, K2O 1.2-1.6% and SO3 3.5-4.5%, and the rest is loss on ignition.
2. The alkali-resistant soft porcelain according to claim 1, characterized in that: The particle size of the artificial stone waste is less than 3 mm.
3. The alkali-resistant soft porcelain according to claim 1, characterized in that: The emulsion A includes any one of silicone-acrylic emulsion, pure acrylic emulsion and styrene-acrylic emulsion; The emulsion B includes any one of silicone-acrylic emulsion, pure acrylic emulsion and styrene-acrylic emulsion.
4. The alkali-resistant soft porcelain according to claim 1, characterized in that: The mesh number of the silicon micropowder is 800 to 2000 mesh; The mesh number of the quartz sand is 70-120 meshes, the mesh number of the quartz powder is 200-400 meshes, and the mesh number of the heavy calcium carbonate powder is 200-400 meshes.
5. The alkali-resistant soft porcelain according to claim 1, characterized in that: Also includes a finishing layer, the finishing layer is located on the top of the surface layer, and the finishing layer is obtained by curing the finishing hydrophobic coating; Calculated by weight, the topcoat hydrophobic coating includes the following raw materials: 40 to 60 parts of silica sol, 1 to 3 parts of surfactant, 35 to 50 parts of silane coupling agent, 1 to 3 parts of solvent and 0.5 to 2 parts of hydrophobic additive.
6. The alkali-resistant soft porcelain according to claim 5, characterized in that: The particle size of the silica sol is 5 to 50 nm.
7. The alkali-resistant soft porcelain according to claim 5, characterized in that: The hydrophobic auxiliary agent is a self-crosslinking modified polysiloxane, and the surfactant is a polyethylene glycol type nonionic surfactant.
8. The alkali-resistant soft porcelain according to claim 5, characterized in that: The thickness of the bottom layer is 1-1.5 mm, the thickness of the surface layer is 1.6-2 mm, and the thickness of the overcoat layer is 30-90 μm.
9. A method for preparing alkali-resistant soft porcelain, characterized in that: The method for preparing the alkali-resistant soft porcelain according to any one of claims 5 to 8 comprises the following steps: S1. According to the formula of the bottom slurry, the water reducing agent and water are mixed in a formula amount to obtain a first mixture; the emulsion A and emulsion B are added to the first mixture and mixed evenly to obtain a first intermediate material; the cement-based ceramic waste residue, quartz sand, quartz powder and heavy calcium carbonate powder are added to the first intermediate material and mixed evenly to obtain a bottom slurry; S2. According to the formula of the surface slurry, the water reducing agent and water are mixed in the formula amount to obtain a second mixture; the emulsion A and emulsion B are added to the second mixture and mixed to obtain a second intermediate material; the silicon powder, quartz sand, quartz powder and heavy calcium carbonate powder are added to the second intermediate material and mixed to obtain a surface slurry; S3. According to the formula of the overlay hydrophobic coating, the formula amount of silica sol, surfactant, silane coupling agent, solvent and hydrophobic additive are mixed uniformly to obtain an overlay hydrophobic coating; S4. Inject the surface layer slurry into the mold, and form a surface layer after curing at 85-110°C for 0.12-0.2h; inject the bottom layer slurry on the surface of the surface layer, and form a bottom layer after curing at 85-110°C for 0.8-0.95h, and obtain a soft porcelain intermediate after demoulding; spray the top hydrophobic coating on the top of the surface layer in the soft porcelain intermediate to form a top layer, and obtain an anti-alkali soft porcelain after curing.
Citation Information
Patent Citations
Artificial stone made through using solid waste residues
CN103204663A
Cement-based artificial stone containing artificial stone waste residues and preparation method thereof
CN116462464A
Waterproof slurry for wear-resistant polymer cement for exposure and preparation method thereof
CN107417197A
Lightweight high-hardness flexible ceramic decorative material and preparation method thereof
CN107555867A
Floor tile laying adhesive material as well as preparation method and application thereof
CN109836098A
